Genetics of ovulatory dysfunction and infertility: a scoping review and gene ontology analysis - DiPietro, Erin E.; Sarasua, Sara M.; Hopkins, Casey S.; Ganakammal, Satishkumar Ranganathan; Boccuto, Luigi; Hurwitz, Joshua (Frontiers in Endocrinology, 2025)
BackgroundThe genetic components of the etiologies of ovulatory dysfunction-related infertility (ODRI) are poorly characterized.ObjectivesThis paper aimed to comprehensively identify, compile, and categorize published research on relationships between genetics and ovulatory-related infertility in humans.MethodsA scoping review was performed on research articles relating human genes, ovulatory dysfunction, and infertility retrieved from PubMed and Web of Science databases. A total of 45 articles were included in the study. The data has been organized into three categories based on relevant findings: polycystic ovary syndrome (PCOS), premature ovarian insufficiency (POI), and other diagnoses related to ovulatory dysfunction and infertility.ResultsSources revealed 235 different genes linked to ovulatory dysfunction and infertility including follicle-stimulating hormone receptor (FSHR), luteinizing hormone/choriogonadotropin receptor (LHCGR), and bone morphogenic protein 15 (BMP15). PCOS-related articles revealed variants in genes with functions focused on androgen production, such as LHCGR and FSHR. POI-related articles revealed variants in genes with functions focused on folliculogenesis and pubertal development, such as BMP15 and STAG3, stromal antigen 3. The “other” category revealed genes resulting in enzyme deficiencies interacting with a wide range of functions.ConclusionsIn this review, we have highlighted the extreme variability in what is known about the genetics of ODRI by compiling and categorizing genes identified in the literature as associated with ODRI and its associated subtypes. We have also provided a comprehensive list of ODRI genes specifically identified in humans. The findings from this review, specifically the list of ODRI genes, can be used for targeted gene panel development in assisted reproductive technology to improve clinical testing and diagnosis, as well as in developing individualized treatment strategies for ODRI patients.